BLENDED LEARNING: COMBINING TRADITIONAL AND DIGITAL METHODS IN ENGLISH LANGUAGE TEACHING - Fayzullayeva Dilorom Sanjarbek qizi (Modern American Journals, 2025)
This paper explores the integration of blended learning in English Language Teaching (ELT), combining traditional face-to-face instruction with digital tools. The study was conducted in three academic lyceums in Tashkent, where teachers implemented blended approaches using platforms like Moodle, Zoom, and Quizlet. Findings suggest that blended learning improves student engagement, enhances independent learning, and supports differentiated instruction. Despite challenges such as unequal access to technology and the need for teacher training, the results demonstrate the potential of blended learning to enhance the quality of English language education. Recommendations are provided for effective implementation in secondary and higher education contexts.
Keywords: Blended learning, English Language Teaching (ELT), digital tools, traditional instruction, student engagement, educational technology, hybrid teaching.